Training of Teachers – Search for Appropriate Instructional Strategy - Mishra, S.K. (JOURNAL OF INDIAN EDUCATION, 2015)
Presently the training of both prospective and practising teachers is very weak. One of the main factors contributing to this situation is that teachers are trained in a way that students in schools are taught. This is based on the premise that learning behaviour of both adults and students is the same. This is an erroneous assumption. There are researches which now reflect that children and adults learn in fundamentally different ways. There are now two sciences– Pedagogy and Andragogy. The former is the art and science of helping children to learn and the latter stands for art and science of helping adults to learn. For an effective training of both prospective and practising teachers, Andragogy needs to be used failing which the human and material resources invested would not result in expected dividends. Adults’ training needs to be based on six (6) principles. Teacher educators should adhere to these principles while training teachers. One of these principles is that training of teachers should be problem centred rather than subject centred. This is based on the fact that adults possess vast knowledge and experience when they come to the training situation. They want to invest these experiences in the teaching learning process. If they are subjected to lecturing, they hardly take interest in the learning experiences. Further, like children adults also learn in number of ways rather than in one way. Adults also need physical comfort in the learning situation. The relationship between an adult learner and adult trainer has to be different from that of a student and teacher in a school.